2016
DOI: 10.1155/2016/5173205
|View full text |Cite
|
Sign up to set email alerts
|

HMBA Enhances Prostratin-Induced Activation of Latent HIV-1 via Suppressing the Expression of Negative Feedback Regulator A20/TNFAIP3 in NF-κB Signaling

Abstract: In the past decade, much emphasis has been put on the transcriptional activation of HIV-1, which is proposed as a promised strategy for eradicating latent HIV-1 provirus. Two drugs, prostratin and hexamethylene bisacetamide (HMBA), have shown potent effects as inducers for releasing HIV-1 latency when used alone or in combination, although their cellular target(s) are currently not well understood, especially under drug combination. Here, we have shown that HMBA and prostratin synergistically release HIV-1 lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
(56 reference statements)
1
10
1
Order By: Relevance
“…Results of the present study also show that the deleterious effects of HMBA on NK-cell phenotype and function may have negative implications for its employment in HIV-1 eradication strategies. The potential of HMBA in the reversal of HIV-1 latency has been recently reported, especially when combined with a second LRA belonging to a distinct functional category such as PRO 42 , 43 . By using a primary CD4 + T-cell based model of HIV-1 latency, we found that HMBA was devoid of the capacity to reactivate the virus when used alone or in combination with PRO, which is in contrast with previous reports 42 , 43 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of the present study also show that the deleterious effects of HMBA on NK-cell phenotype and function may have negative implications for its employment in HIV-1 eradication strategies. The potential of HMBA in the reversal of HIV-1 latency has been recently reported, especially when combined with a second LRA belonging to a distinct functional category such as PRO 42 , 43 . By using a primary CD4 + T-cell based model of HIV-1 latency, we found that HMBA was devoid of the capacity to reactivate the virus when used alone or in combination with PRO, which is in contrast with previous reports 42 , 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The potential of HMBA in the reversal of HIV-1 latency has been recently reported, especially when combined with a second LRA belonging to a distinct functional category such as PRO 42 , 43 . By using a primary CD4 + T-cell based model of HIV-1 latency, we found that HMBA was devoid of the capacity to reactivate the virus when used alone or in combination with PRO, which is in contrast with previous reports 42 , 43 . Conflicting results are possibly due to differences in model systems and method of quantification, consisting in intracellular p24 + accumulation in primary T cells (this study) as opposed to HIV-1 Long terminal repeat (LTR)-driven transcription in T-cell lines 43 , or genomic viral RNA levels in culture supernatant of PBMCs from ART-treated patients 42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bryostatin-1 also synergized with JQ1 in cell lines in vitro and patient cells ex vivo (28; 84). The PKC agonist prostratin has shown similar synergistic activity when combined with HDAC inhibitors(85), JQ1 (a BRD domain inhibitor) (28; 86), hexamethylene bisacetamide (HMBA, a P-TEFb release enhancer) (87) and a TLR-8 agonist (88). Ingenol B has demonstrated synergy with JQ1 in patient cells ex vivo (84).…”
Section: Lra Combination Therapymentioning
confidence: 99%
“…Beyond concerns regarding integration site heterogeneity, the immortalized nature of the J-Lat cell line may impact molecular and regulatory pathways that affect HIV latency. However, the widespread usage of the J-Lat model and its derivative clones to examine viral latency and to evaluate the efficacy of HIV cure strategies in vitro speak to the model's utility (51)(52)(53)(54)(55)(56)(57)(58)(59)(60). Ample data from primary cell-based models of latency and experiments involving ex vivo administration of LRAs to cells obtained from HIV-infected individuals on ART suggest that differences between applied models and between individuals can have dramatic effects on the establishment, maintenance, and reversal of HIV latency (43,61,62).…”
Section: Discussionmentioning
confidence: 99%